Impact of social media marketing activity on brand loyalty - Yunanto, Wahyu; Apsari Sugiat, Maria; Ariyanti, Maya (Goodwood Publishing, 2025)
Purpose: This study examines the effectiveness of Social Media Marketing Activities (SMMA) in enhancing brand loyalty at PT. Mumpuni Inti Mandiri. It evaluates customer perceptions of SMMA, self-brand connection, brand equity, brand trust, and their influence on brand loyalty. Method: A quantitative positivist approach was applied. Data were gathered through online surveys targeting PT customers. Mumpuni Inti Mandiri. Structural equation Modelling (SEM) using Partial Least Squares (PLS) via SmartPLS 3.2.6 was employed to analyze the data. Validity and reliability tests ensured the accuracy of the instruments. The hypotheses were tested using one-tailed T-statistics. Results: The results show that Customer perceptions of SMMA, self-brand connection, brand equity, brand trust, and brand loyalty were in the high category. SMMA significantly influences self-brand connection, brand equity, and brand trust. Moreover, brand loyalty is affected both directly and indirectly by these mediators. This implies that PT. Mumpuni Inti Mandiri’s social media strategies are effective in fostering emotional connection, consumer trust, and long-term loyalty. Conclusions: SMMA plays a vital role in building brand loyalty by enhancing brand-related psychological factors. Integrated social media marketing efforts have proven to be valuable in creating strong brand-consumer relationships. Limitations: The study’s scope was limited to one company and used self-reported survey data, which may affect generalizability. Contribution and Novelty: This study introduces an integrated model that connects SMMA with brand loyalty through emotional and cognitive pathways, offering insights into effective digital branding strategies in emerging markets.